Search for TeV-scale gravity signatures in high-mass final states with leptons and jets with the ATLAS detector at s√=13 TeV - Aaboud, M. (2016)
A search for physics beyond the Standard Model, in final states with at least one high transverse momentum charged lepton (electron or muon) and two additional high transverse momentum leptons or jets, is performed using 3.2 fb−1 of proton--proton collision data recorded by the ATLAS detector at the Large Hadron Collider in 2015 at s√=13 TeV. The upper end of the distribution of the scalar sum of the transverse momenta of leptons and jets is sensitive to the production of high-mass objects. No excess of events beyond Standard Model predictions is observed. Exclusion limits are set for models of microscopic black holes with two to six extra dimensions.